BACILLUS CALMETTE-GUERIN (BCG) LYMPHADENITIS- CHANGING TRENDS AND MANAGEMENT - Nazir, Zafar; Qazi, Saqib Hamid (Journal of Ayub Medical College Abbottabad, 2005)
Background: Bacillus Calmette-Guérin (BCG) vaccination is performed as a part of expanded Programme of Immunization (EPI). Suppurative lymphadenitis is the common complication of BCG vaccination. The optimum treatment for this complication is debated. Methods: All cases of BCG lymphadenitis presenting to pediatric surgical service over a 17-year study period were reviewed to determine the optimum treatment for this problem. Results: Sixty children were referred for the management of BCG lymphadenitis during the study period. Most patients (n=43) presented during 1988 and 1990. Children were healthy and received BCG (Pasteur strain) vaccination at EPI during first 2 months of life. Initially all the patients received medical treatment with anti-tuberculous drugs for one to nine months. Fifty-two children who presented with large (~ 3cm) fluctuant lymph nodes, required a surgical procedure to avoid spontaneous rapture and sinus formation (Group A), whereas medical treatment was effective in five out of eight patients presenting with small (~1 cm) nodes (Group B). Conclusions: Medical treatment with antituberculous drugs is not effective to treat BCG lymphadenitis, when the involved lymph nodes are around 3.0 cm and have developed fluctuation and inflammation of over lying skin. Keywords: Vaccination, BCG vaccine, Lymph node, Lymphadenitis